Evaluating the beads of life groups: hearing from our participants. (January 2023) - Valentino, Charlotte; Daniilidi, Xeni; Portnoy, Sara
Introduction and Aims: The Beads of Life (BOL) approach uses a narratively informed methodology 'to enable children and young people to make sense of their cancer journey in ways that make them stronger'. We will share feedback from BOL groups and reflect on changes made over time. Method: Between 2014 and 2019, we have run 14 groups. Participants were aged 13–25, had received a diagnosis of cancer and were either on or had completed treatment. Quantitative and qualitative feedback was gathered at each workshop and 1 month later, with qualitative data then being analysed using thematic analysis. Results: 106 young people attended the groups. Young people reported that sharing experiences of cancer was useful, that they enjoyed the group and that they were highly likely to recommend it to others. Feedback remained consistent a month post-intervention. Qualitative feedback showed the value young people placed on meeting others, sharing their stories and on things they learnt about themselves from the group. Discussion: Themes support the intention of the intervention to provide a safe space for young people to share and reflect on their cancer journey, to connect with others and to enable peer support and mutual learning.